INTERPERSONAL COMMUNICATION BETWEEN INSTRUCTOR AND MEMBER IN RUNNING HEALTHY LIFESTYLES AT FITNESS HOTEL GRAND ELITE PEKANBARU - Andi Muhammad Adha; Nita Rimayanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Everyone wants to keep their health for the sake of fitness. Therefore, for many healthy lifestyles that choose sports activities in the gym. Fitness is the place of choice to be able to form a healthy body, maintain a healthy lifestyle also foster relationships with friends and people in the gym. Relationships are not only between members but also a close relationship between the instructor and the members. Interpersonal communication is dyadic communication that only two people, such as husband wife, two close friends, teacher-students, as well as instructors and fitness members. The characteristics of communication dyadic with parties who communicate are at close range and parties who communicate and receive messages simultaneously and spontaneously both verbally and nonverbally. This study aims to find out how the interpersonal communication of instructors and members in running the lifestyle of fitness at Grand Elite Hotel Pekanbaru.This research uses qualitative descriptive research method. Informants in this research are 2 instruktur and 5 member by using purposive sampling technique. Data finishing technique using participant observation, interview and documentation. In achieving the validity of the data in this study, researchers used extension of participation and triangulation.The results of research indicate the existence of interpersonal communication of the instructor and the members are running well. Firstly, the openness of the instructor and the members does not take long to get to know each other and the members in an average time of 14 days can already feel comfortable and confident the problems associated with physical problems. They. Secondly, empathy is when members give an opinion that the instructor has a good sense of empathy in the perceived problems of the members and in the training. Third, the attitude of support with the attitude and behavior of instructors while motivating members and communication styles they use are easy to understand and not offend members. Fourth, the positive attitude is proved by the absence of complaints from members of the attitude, character and style of instructors At the Grand Hotel Elite Hotel Pekanbaru. Fifth, the equality is more dominated by the instructor of the members, but the instructor is still open to accept suggestions and feedback from members..Keywords: Interpersonal Communication, Running Healthy Lifestyle, Instructor and Member